For the Safety of Fresh Produce: Regulatory Considerations for Canada on the Use of Whole Genome Sequencing to Subtype Salmonella - Ngueng Feze, Ida; Dalpé, Gratien; Song, Lingqiao; Farber, Jeff; Goodridge, Lawrence; Levesque, Roger C.; Joly, Yann (Frontiers in Sustainable Food Systems, 2018)
Salmonella is one of the oldest bacteria known to man, yet it is also one of the most prevalent when it comes to foodborne-related diseases and outbreaks. Naturally present in the environment and difficult to treat on fresh produce, Salmonella represents an important food safety challenge. Emerging technologies such as whole genome sequencing (WGS) and next generation sequencing (NGS) now offer promising applications within the realm of food safety that can significantly change the way routine testing, inspections and disease surveillance are done. They offer potential avenues that may foster more sustainable agricultural and environmental practices to detect and reduce the presence of Salmonella. Strategies are being developed to better cluster, integrate and share genomic data to facilitate the development of diagnostic tests and control methods, as well as generate robust evidence to better inform future policy and regulatory decision-making. Using the approaches developed by the Salmonella Syst-OMICS consortium, a large-scale Canadian-based genomic project, this paper discusses the policy and regulatory considerations for the applications of WGS and NGS technologies in the development of testing and biocontrol tools for food safety. The paper presents an overview of the current regulatory framework for the approval of testing methodologies for Salmonella. It discusses considerations related to (1) the development of a new test for Salmonella, (2) the potential establishment of a Salmonella risk virulence classification scheme, and (3) the development of a biocontrol method to reduce the presence of Salmonella on fresh produce.